2011
DOI: 10.1136/oem.2010.063503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of job strain on fatigue: cross-sectional and prospective views of the job content questionnaire and effort–reward imbalance in the GAZEL cohort

Abstract: These analyses continue to validate the various subcomponents scales of workplace stress as measured by the JCQ and effort-reward imbalance model in GAZEL. They also highlight the importance of psychosocial work factors in the experience of overall fatigue even after an 8-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 46 publications
4
23
1
Order By: Relevance
“…This contradicts previous findings demonstrating reduced rather than enhanced self-reported health among overcommitted workers [18, 25, 26]. In the Italian sample, mean scores of “overcommitment” were not very high, and this fact may prevent the detection of adverse health effects.…”
Section: Discussioncontrasting
confidence: 95%
“…This contradicts previous findings demonstrating reduced rather than enhanced self-reported health among overcommitted workers [18, 25, 26]. In the Italian sample, mean scores of “overcommitment” were not very high, and this fact may prevent the detection of adverse health effects.…”
Section: Discussioncontrasting
confidence: 95%
“…The results of previous studies on sleep disturbance and fatigue, two common consequences of psychosocial stress, were consistent with the ERI model 4,22) . A study of female critical care nurses also showed an association between poor sleep quality and fatigue 23) .…”
Section: Discussionsupporting
confidence: 88%
“…Stress levels among professional nurses have increased in recent years due to the demands of clinical nursing. Previous studies have shown that work demands and stress are associated with adverse mental health such as emotional exhaustion 1) , depressive disorder 2,3) and fatigue 4,5) , which result in sleep problems and sickness absence 1) . Stress systems in the body, like the sympathetic-adrenomedullary system and the hypothalamic-pituitary-adrenocortical axis, start working, using adapted processes as the stress attracting 6) , and exhaustion tend to result from longterm exposure.…”
mentioning
confidence: 99%
“…The relationship leading from effort-reward imbalance to impaired health complaints has received ample attention in occupational health research (e.g. Feldt et al, 2013;LavoieTremblay et al, 2008;Sembajwe et al, 2012;Van Vegchel, De Jonge, Bosma, et al, 2005). This effect is generally understood as resulting from experienced negative emotions, such as anger and frustration related to failed reciprocity.…”
Section: Effort-reward Imbalancementioning
confidence: 99%